Hubungan Gaya Belajar dengan Prestasi Akademik Siswa SMP - Fitri; Faizatul Akila; Gusmaneli (CV. ITTC INDONESIA, 2025)
Learning style is a crucial factor in the learning process, contributing to the academic success of junior high school students. Each student has different learning styles, such as visual, auditory, or kinesthetic. This diversity requires teachers to design learning strategies that accommodate students' learning needs so that learning objectives can be optimally achieved. A mismatch between learning styles and teaching methods has the potential to reduce student motivation, engagement, and academic outcomes. Furthermore, issues arising in schools, such as limited media, lack of teacher training, and limited understanding of learning styles among students and parents, contribute to their implementation. Therefore, optimizing learning styles requires early identification of student learning characteristics, the use of varied learning media, active learning, and collaboration between schools and families. With appropriate, evidence-based strategies, implementing learning styles is expected to improve the quality of the learning process and the academic achievement of junior high school students in a more equitable and sustainable manner.